Symbiosis theory-directed green synthesis of silver nanoparticles and their application in infected wound healing - Wen L (Dove Medical Press, 2016)
Lu Wen,1 Pei Zeng,1 Liping Zhang,1 Wenli Huang,1 Hui Wang,2 Gang Chen1 1Department of Pharmaceutics, School of Pharmacy, 2School of Traditional Chinese Medicine, Guangdong Pharmaceutical University, Guangzhou, People’s Republic of China Abstract: In this study, silver nanoparticles (AgNPs) were synthesized for the first time using an antibacterial endophytic fungus of Chinese medicinal herb Orchidantha chinensis, which has anti-inflammatory and antimicrobial activities. The AgNPs were analyzed by various characterization techniques to reveal their morphology, chemical composition, and stability. Also, the relationship between Chinese medicinal herbs, endophytic fungi, and the property of AgNPs was investigated for the first time. Interestingly, an experiment performed in this study revealed the proteins produced by the endophytic fungus to be capped on the nanoparticles, which led to an increase in the stability of spherical and polydispersed AgNPs with low aggregation for over 6 months. More importantly, further study demonstrated that the AgNPs possessed superior antibacterial activity and effectively promoted wound healing. Altogether, the biosynthesis of active AgNPs using the endophytic fungus from Chinese medicinal herb based on the symbiosis theory is simple, eco-friendly, and promising. Keywords: silver nanoparticles, Orchidantha chinensis, endophytic fungi, symbiosis theory, wound healing